Philosophy of Mind/Philosophie de l’esprit
X, 470 p.
Keywords: This publication is a continuation of two earlier series of chroni cles, Philosophy in the Mid-Century (Firenze 1958/59) and Con temporary Philosophy (Firenze 1968), edited by Raymond Kli bansky. Like the other series, these chronicles provide a survey of important trends in contemporary philosophical discussion from 1966 to 1980. The need for such surveys has, I believe, increased rather than decreased over the last years. The philosophical scene appears, for various reasons, more complex than ever before. The continuing process of specialization in most branches, the emergence of new schools of thought, particularly in philosophical logic and the philosophy of language, the convergence of interest (though not necessarily of opinion) of different traditions upon certain prob lems, and the increasing attention being paid to the history of philosophy in discussions of contemporary problems are the most important contributory factors. Surveys of the present kind are a valuable source of knowledge of this complexity and may as such be an assistance in renewing the understanding of one's own phi losophical problems. The surveys, it is to be hoped, may also help to strengthen the Socratic element of modem philosophy, the dialogue or Kommunikationsgemeinscha/t. • So far, four volumes have been· prepared for the new series. The present chronicles in the Philosophy of Mind (Vol. 4) follow upon chronicles in the Philosophy of Language and Philosophical Logic (Vol. 1) and chronicles in the Philosophy 0/ Science (Vol. 2) and chronicles in the Philosophy 0/ Action (Vol. 4).